Komponen Usahatani Pendukung Penerapan Peningkatan Indeks Pertanaman pada Beberapa Agroekosistem - Purnamayani, Rima; Wira Etika, Adhe Phoppy; Syahbuddin, Haris (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
ncreasing the cropping index is a strategic policy and program to increase the efficiency of available land use.  Referring to the potential and constraints of cropping index improvement, it is necessary to review the supporting components that affect cropping index implementation improvement in some agroecosystems. The purpose of this study was to aims to analyze the components of farming that support the implementation of increased cropping index in upland, rainfed lowland, and swampy land. This activity was carried out in five provinces namely Banten, West Java, DI Yogyakarta, East Nusa Tenggara, and South Sumatra from August to December 2018. The site selection was done purposively based on agroecosystems. The collected data were tabulated and analyzed using quantitative and qualitative approaches then interpreted descriptively and analyzed with multiple linear regression analysis. The dependent variable (Y) is the cropping index and the independent variables (xi) are labor, water availability, demonstration plot capital availability, water resources, supervisory, and extension media. The results of the combined linear regression analysis showed that water availability and supervisory were the supporting components that have a significant effect on every agroecosystem.  Meanwhile, water, capital and labour availability were variables that have a significant effect on the implementation of increased cropping index in upland agroecosystems.  The dissemination media has a significant effect only on rainfed lowland, while the capital  availability and water sources were supporting components that have a significant effect at  swampy land.